Psychological aspects of precocious puberty child during the COVID-19 pandemic - Nurul Ima Suciwiyati; Nur Rochmah; Muhammad Faizi; Fadhil Abiyyu Yofi (Majalah Obstetri & Ginekologi, 2022)
HIGHLIGHTS 1. Presents a longitudinal case of a child with Organic Central Precocious Puberty (CPP).2. Focused on psychological aspect during the COVID-19 pandemic.   ABSTRACT Objective: To present a longitudinal case of a child with organic Central Precocious Puberty (CPP) that focused on medical, growth and development, and parent’s psychological aspect during the COVID-19 pandemic. Case Report: A 14-month old girl attended with major complaints of breasts enlargement and menstruation. The Tanner's stage was at A1M3P1 and the vagina showed reddish-brown spots. The patient’s bone age was advanced (3 years and 6 months). USG examination showed a corpus uterine: cervix ratio of 2:1. GnRH stimulation test showed an elevated of FSH/LH and estradiol. MRI showed an extra-axial dense mass that leads to Hypothalamic Hamartoma (HH). The definitive diagnosis of this patient was organic CPP with HH. The patient was managed with GnRH analog. Precocious puberty (PP) becomes a financial and psychosocial burden for parents. The COVID-19 pandemic adds a double burden for the parents. Conclusion: During the COVID-19 pandemic, parents with PP children had a good psychological aspect if the child was comprehensively handled with adequate motivation and psychoeducation.